Sports activity as a means of forming anti-stress resistance of students in an educational environment - Spiridonov E.A.,; Mironov A.O.,; Ponimasov O.E.,; Saiganova E.G., (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increasing stress resistance of students on the basis of the development of emotional stability, adaptability of thinking and self-regulation in the process of zonation sports activities. Methods and structure of the study. The research program of studying students reactions to various external stimuli is focused on identifying the potential of sports activity, which contributes to increasing personal self-esteem and the ability to manage stress. The diagnostic complex includes: the Spielberg-Khanina self-assessment methodology, the Eysenka test-questionnaire, the SAN test of psychoemotional reactions to stress. Results and conclusions. A significant correlation of stress resistance with the SAN index (0,578), the ability to self-regulate (0,476), the level of subjective control (0,556) and a negative correlation with emotional lability (0,458) and the level of anxiety (0,632) was established. A system of sports and recreational activities has a high formative potential in achieving stress resistance of students.